General and orofacial aspects of pychnodysostosis: report of two dental surgical intercurrences (Research, Society and Development, 2021)
The aim of this article is to discuss the clinical, diagnostic and treatment aspects of dental surgical complications in patients with pychnodysostosis, through two clinical cases. Female patient, with physical characteristics of pychnodysostosis, 27 years old, complaining of pain, which appeared after undergoing a tooth extraction in the region of element 38. After clinical and radiographic examinations, a mandible fracture was found in the procedure site. The fracture was treated using a submandibular approach and fixation with a reconstruction plate, but without showing radiographic signs of reliable bone consolidation. The second case is a 23-year-old female patient with pychnodysostosis, who reported recurrent pain in the left mandibular body and frequent odors from the oral cavity, after undergoing a tooth extraction that had not healed. The treatment of the symptoms presented was performed using a delicate curettage at the site, where the presence of a cleavage plane was observed. The specimen was sent for histopathological analysis, which later showed a picture compatible with osteomyelitis with foci of bone necrosis. To date, the current literature does not present a description of a detailed clinical protocol for patients with this condition. However, some precautions must be taken to prevent bone fractures, such as avoiding mechanical trauma and invasive surgical approaches, in addition to maintaining regular dental follow-up.